Skill Requirements across Firms and Labor Markets: Evidence from Job Postings for Professionals - Deming, David; Kahn, Lisa B. (Journal of Labor Economics, 2018)
We study variation in skill demands for professionals across firms and labor markets. We categorize a wide range of keywords found in job ads into 10 general skills. There is substantial variation in these skill requirements, even within narrowly defined occupations. Focusing particularly on cognitive and social skills, we find positive correlations between each skill and external measures of pay and firm performance. We also find evidence of a cognitive social skill complementarity for both outcomes. As a whole, job skills have explanatory power in pay and firm performance regressions beyond what is available in widely used labor market data.